The Regulation of Carbonic Anhydrase and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase Activase by Light and CO2 in Chlamydomonas reinhardtii. - Rawat, M. (1995)
We have investigated the regulation of accumulation of ribulose-1,5-bisphosphate carboxylase/oxygenase activase and the periplasmic carbonic anhydrase (CA) in Chlamydomonas reinhardtii. In algae, the periplasmic CA is required for efficient CO2 fixation when the CO2 concentration is low. These two proteins are affected differently by the CO2 level in the environment. The steady-state level of the ribulose-1,5-bisphosphate carboxylase/oxygenase activase transcript was only slightly and transiently affected by a reduction in ambient CO2 concentration, whereas the CA transcript level was strongly induced by air containing ambient (350 parts per million) CO2 (low CO2) conditions. The transcripts for both proteins showed strong oscillations when the alga was grown under a 12-h light/12-h dark growth regime, with the transcripts encoding these proteins present just before the onset of the light cycle. The observation that the CA transcript was made in the dark was surprising, since earlier reports indicated that active photosynthesis was required for the induction of the periplasmic CA. Further experiments demonstrated that the CA transcript was partially induced under low-CO2 conditions even when the switch to low CO2 was done in the dark. Our results suggest that C. reinhardtii might sense the CO2 concentration in a more direct manner than through C2 or C3 cycle intermediates, which has been previously suggested.